2018
DOI: 10.1080/17445647.2018.1425164
|View full text |Cite
|
Sign up to set email alerts
|

Geology, slow-moving landslides, and damages to buildings in the Verbicaro area (north-western Calabria region, southern Italy)

Abstract: This paper presents a mass movement inventory map at 1:5000 scale of the Verbicaro area (about 13 km 2 ) located in the Calabria region (southern Italy). The Main Map results from the visual interpretation of aerial photographs, multi-temporal geomorphological field surveys, and field investigations of damage suffered by buildings. Some 53% of the study area is affected by a total of 252 landslides, comprising different types, state of activity, and size. The mapped landslides, mainly complex type, involve low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…The hilly and mountainous central part of the Freetown Layered Complex has documented more landslide events and caused colossal losses (UNDP and EPA, 2017; Bruce 2019) than any other place within the Layered Complex (FCC 2014;INTEGEMS 2017;Arup, BGS, JBA, and INTEGEMS, 2018). One such incident was the Regent landslide which affected the Sugarloaf Mountain and claimed more lives (i.e.1, 100 people) than anywhere globally in 2017 (Redshaw et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The hilly and mountainous central part of the Freetown Layered Complex has documented more landslide events and caused colossal losses (UNDP and EPA, 2017; Bruce 2019) than any other place within the Layered Complex (FCC 2014;INTEGEMS 2017;Arup, BGS, JBA, and INTEGEMS, 2018). One such incident was the Regent landslide which affected the Sugarloaf Mountain and claimed more lives (i.e.1, 100 people) than anywhere globally in 2017 (Redshaw et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2). From the geological point of view, the prevailing Frido Unit, constituted by low-grade metamorphic rocks usually marked by extensional brittle-ductile shear zones, includes metapelites, phyllites, shales and metalime-stones; it tectonically overlays the Lungro-Verbicaro Unit that outcrops in correspondence of the historic centre (Amodio Morelli et al 1976;Borrelli et al 2018;Ferlisi et al 2015;Nicodemo et al 2017Nicodemo et al , 2018. At the top of the units, locally covered by colluvial deposits, blocks and fragments of metamorphic rocks in a prevalently clayey matrix can be found.…”
Section: Medium Scalementioning
confidence: 99%
“…in the urban area as well as the slow-moving landslide inventory map, drawn up by Borrelli et al (2018) at 1:5000 scale. Based on the outcomes of previous studies concerning the Calabria region (Sorriso-Valvo 1993; Antronico et al 1996;Greco et al 2007;Gullà et al 2017b), the mapped landslides are classified as: roto-translational slides, complex landslides, and landslide zones (Fig.…”
Section: Medium Scalementioning
confidence: 99%
“…Slow-moving landslides are observed worldwide in many countries, e.g. Italy (Cascini et al, 2008;Antronico et al, 2015;Uzielli et al, 2015a;Borrelli et al, 2018;Ferlisi et al, 2019), Canada (Clifton et al, 1986;Brooker and Peck, 1993;Moore et al, 2006;Barlow, 2000), China (Chen et al, 2016;Zhang et al, 2018;Dong et al, 2018;Wang et al, 2018), the USA (Esser, 2000), and Australia (Jworchan et al, 2008). Fell et al (2008) suggested the estimation of the physical vulnerability of elements at risk for various landslide types.…”
Section: Introductionmentioning
confidence: 99%